The diagnostic accuracy of the faecal immunohistochemical test in identifying significant bowel disease in a symptomatic population. (30th November 2021) - MacDonald, Scott; MacDonald, Linda; Godwin, Jon; Macdonald, Angus; Thornton, Michelle
Abstract: Aim: Provisional research on the faecal immunohistochemical test (FIT) for symptomatic colorectal patients has shown a high negative predictive value but has lacked long‐term patient follow‐up, raising the possibility of missed diagnoses of colorectal cancer (CRC). The aim of this work is to describe the long‐term diagnostic accuracy of the FIT for CRC and significant bowel disease (SBD) in a symptomatic population in NHS Lanarkshire. Method: From October 2016 to February 2019, all primary care referrals of symptomatic colorectal patients in NHS Lanarkshire were asked to provide a FIT. The baseline demographics, investigations and diagnoses for each patient were prospectively completed until February 2021. A FIT result of ≥10 μg haemoglobin (Hb)/g faeces was considered to be positive. Results: A total of 5250 patients were identified (median age 62 years; 46% male; median follow‐up 31 months) with 65.1% (3418) being FIT negative. The SBD rate was 6.2% and the CRC rate was 2.9% (151). The SBD rate was significantly higher in the FIT‐positive group (13.8% vs. 2.2%; p  < 0.001) and 32.9% of patients with FIT ≥ 400 μg Hb/g had SBD. The sensitivity of FIT ≥ 10 μg Hb/g for CRC was 87.4% and for SBD it was 76.9%. Specificity was 66.6% and 66.7%, and the negative‐predictive value was 99.4% and 97.7%, respectively. Sensitivity for CRC could theoretically be increased to 94.8% if FIT‐negative patients were to undergo flexible sigmoidoscopy. Conclusion: A FIT‐only referral pathway for symptomatic colorectal patients will miss over 12% of cancers and over 23% of SBD. Theoretically, combining FIT‐negative patients with flexible sigmoidoscopy increases the sensitivity for CRC. The FIT offers a mechanism for prioritizing patient access to investigations, particularly in resource‐limited areas; however, further work to identify FIT‐negative patients diagnosed with CRC is required.